(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2020)
The present Research work is related to the intercultural realities among the women of the Miskito, Creole, and Mestizo ethnic groups in the city of Bilwi, Puerto Cabeza Municipality, RACCN. The city of Bilwi is characterized by being multiethnic and multilingual. Due to the diversity of ethnicities present within the population, from the cosmovision of coastal women, their daily life and intercultural relations with The purpose of identifying how and why they occur, from the perspective of women. What it was possible to identify is that ethnic groups figure women within their cultural practices as indispensable, as well as within their belief and cultural heritage system, the identity of women in terms of their ethnic origins is present, The role of women is strongly linked to the processes of interculturality and the formation of inter-ethnic families open the way to womens perceptions of being a coastal woman within the City of Bilwi. All with the purpose of being able to project the importance of research that encompasses the best understanding of cultures, populations and the social reality that is lived in the Region of the North Caribbean Coast of Nicaragua, from the worldview, experiences and experiences of the The same population of Costa Rica under the eye of women, as they are indispensable for the integral development of the City of Bilwi.